2020
DOI: 10.1136/bmjresp-2020-000729
|View full text |Cite
|
Sign up to set email alerts
|

Utility of established prognostic scores in COVID-19 hospital admissions: multicentre prospective evaluation of CURB-65, NEWS2 and qSOFA

Abstract: IntroductionThe COVID-19 pandemic is ongoing, yet, due to the lack of a COVID-19-specific tool, clinicians must use pre-existing illness severity scores for initial prognostication. However, the validity of such scores in COVID-19 is unknown.MethodsThe North West Collaborative Organisation for Respiratory Research performed a multicentre prospective evaluation of adult patients admitted to the hospital with confirmed COVID-19 during a 2-week period in April 2020. Clinical variables measured as part of usual ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
69
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 20 publications
10
69
0
4
Order By: Relevance
“…However, studies of patients with COVID-19 have shown that 17% mortality occurs among patients with a CURB-65 score of < 2. 27 Bradley et al stated that low CURB-65 scores may not support early COVID-19 discharge, but higher scores are useful for predicting poor outcomes, consistent with our findings. 27 In our study, CURB-65 score on admission was also significantly higher among non-surviving patients than among surviving patients.…”
Section: Discussionsupporting
confidence: 89%
“…However, studies of patients with COVID-19 have shown that 17% mortality occurs among patients with a CURB-65 score of < 2. 27 Bradley et al stated that low CURB-65 scores may not support early COVID-19 discharge, but higher scores are useful for predicting poor outcomes, consistent with our findings. 27 In our study, CURB-65 score on admission was also significantly higher among non-surviving patients than among surviving patients.…”
Section: Discussionsupporting
confidence: 89%
“…The conventional thresholds for positivity of scores above 4, 1 and 0 offered suboptimal sensitivity (0.79, 0.63 and 0.83), with corresponding specificities of 0.69, 0.91 and 0.69. Bradley et al (n=830) 18 reported c-statistics of 0.67 for NEWS2 and 0.74 for CURB-65 as predictors of 30-day mortality, with sensitivities and specificities at conventional thresholds of 0.83 and 0.37 for NEWS2, and 0.80 and 0.59 for CURB-65. Ma et al (n=305) 19 reported c-statistics of 0.79 for NEWS2 and 0.85 for CURB-65 for predicting death.…”
Section: Discussionmentioning
confidence: 99%
“…The recent outbreak of coronavirus disease 2019 (COVID- 19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has challenged healthcare systems worldwide (1). As of , SARS-CoV-2 has results in more than 12.5 million confirmed cases, with more than 2.7 million deaths (2).…”
Section: Introductionmentioning
confidence: 99%